Intelligent chair sensor-actuator: a novel sensor type for seated posture detection and correction - Lucena, Rui (2013)
In order to build an intelligent chair capable of posture guidance and correction we propose a new sensor/actuator pressure cell capable of measuring applied pressure and conformation change, which will allow posture evaluation, guidance and correction. We developed and applied the pressure cells to the seat pad of an office chair to test if both the cells and their placement were suitable for pressure map reconstruction. When tested for 10 different postures, the results showed distinguishable pressure maps for each posture, making the pressure cells suitable for pressure map reconstruction and posture evaluation. This paper also presents a briefly description of our vision and goals for the intelligent chair project.